Geoavailability of heavy metals in sediments of the Chancay and Huaura rivers. Lima Department - Rivera, Hugo (2010)
The present study includes the geochemical-statistical analysis of fourteen heavy metals in active sediments of the Huaura and Chancay rivers, in which the intrusive lithologies of the Batolito de la Costa predominate, and to a lesser extent the lithologies of the Calipuy and Volcánico Casma groups. Likewise, the metals that have a normal distribution are Fe and Cr and the lognormal distribution As-Cu-Cd-Hg-Mo-Ni-Pb-Sb-Sn-V-W-Zn. The average abundance shows that Zn, V, Cr, Pb, Cu are the most abundant metals and Mo, Cd and Hg occurs in small amounts. Pearson's correlation analysis in the Huaura River, the metals that best correlate are As with Cd, Cu, Pb, W, Zn and Cd with Cu and Zn, which indicate that it could have the same origin, while in the Río Chancay the metals do not have a good correlation, which would indicate that they do not have a common origin, except for the Cd with Zn and Fe with V. The Principal Component Analysis determined that of the three components in the Huaura River the most important association is As- Cu-Cd-Zn-Pb-W-Mo and in Río Chancay Cd- Zn-Mo-Ni. Comparing with the limits established for soils in the Dutch Table, the heavy metals in the sediments in the Huaura and Chancay Rivers, which exceed the intervention limits and therefore contaminating arsenic. Comparing the values ​​of the rivers both north and south of the city of Lima, the Rímac river surpasses the intervention values ​​in As, Cu, Zn, Sb, followed by the Chillón River in As, Hg, Sb; the Lurin River in As, Sb; the Río Mala, Chilca, in As, and the Río Omas in Cu.